Penanaman Nilai Agama dan Moral pada Anak Usia Dini dalam Pengasuhan Etnis Jawa dan Melayu di TK Alfia Nur Hamparan Perak - Mhd Habibu Rahman; Sofni Indah Arifa Lubis; Dwi Anggraini (Early Childhood: Jurnal Pendidikan, 2023)
This research is based on the fact that every child's potential will develop rapidly if they receive care that is appropriate to the child's development. The fact is that every ethnicity has different characteristics and parenting styles. For example, Javanese and Malay ethnicity, each of which has its own way of instilling religious and moral values in children from an early age aims to find out the form of instilling religious and moral values in early childhood by looking at the upbringing of Javanese and Malay ethnicities and seeing their relevance to the concept of education. in early childhood. This research method is qualitative with research procedures namely participant observation and in-depth interviews at TK Alfia Nur Hamparan Perak. The research findings show that the form of instilling religious and moral values in early childhood in the upbringing of Javanese and Malay ethnicity both promotes exemplary, habituation and fun storytelling activities. The good figures shown by parents and teachers make it easier for children to understand religious and moral values in their lives. The form of obedience that is instilled by parents in children causes children to obey every order and prohibition from parents in the process of instilling moral and religious values. Teachers at TK Alfia Nur improvise learning through culture that is inherent in children's culture, then ethnic characteristics in parents affect parenting style and have implications for the form of instilling religious and moral values in early childhood. Therefore, the parenting culture that parents receive should not be purely applied to children, nor should it be completely abandoned.